PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SDN 110 PEKANBARU - Risa Nirmalasari; Zariul Antosa; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the low learning outcomes of the VB students at SDN 110 Pekanbaru. It can be seen from their final examination results with an average score of 62,63 when the success criteria is 76. In order to solve this problem, the researcher decided to apply the cooperative learning model Think Talk Write to the students, which starts with the students’ involvement in thinking by themselves after reading the materials provided, followed by reading and developing ideas with their peers and then followed by writing conclusion and reports. This research is an action reserach, which consists of two cycles. Cycle 1 consists of two meetings and one daily exam at the end of every cycle. The subject of this research is the VB students of SDN 110 Pekanbaru which contains of 24 students, consisting of 15 females and 9 males. Before the TTW model was applied, the teachers’ activity in cycle I improved from 66,67%, which is categorized as good, to 75% which is categorized as good as well, and then it improved again in Cycle II and became 95,83% which is categorized as very good. The students’ ;earning outcomes improved from 62,63 to 76,67 in daily exam I and it improved again in daily exam II, becoming 81,25. With the implementation of TTW learning model, the students’ learning outcomes improve by 18,62%, therefore it can be concluded that the implementation of the cooperative learning model Think Talk Write canimprove the learning outcomes of Social Subjects of the VB students at SDN 110 Pekanbaru.Keywords : Cooperative learning, Think Talk Write (TTW) model, Social Subjects’ learningoutcomes